Doing work based research : approaches to enquiry for insider-researchers - Costley, Carol; Elliott, Geoffrey, Dr.; Gibbs, Paul. (Los Angeles : SAGE, 2010)
This book is an authoritative and readable guide to the theory and practice of work based research. Its practical focus provides readers with a substantive guide to considering and enacting research in their own organisations.
Includes bibliographical references and index.
uaj 27/11/2013
Loans
Keywords: Social sciences -- Research; Social sciences -- Research -- Methodology